Peningkatan Kemampuan Membaca Permulaan Menggunakan Media Big Book pada Anak Tunagrahita Ringan Kelas III di SLB Asuhan Kasih Kota Kupang (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve the early reading skills of children with mild intellectual disabilities in Grade III at SLB Asuhan Kasih in Kupang City through the use of big books. The method used is Classroom Action Research (CAR) with a quantitative approach based on the Kemmis and McTaggart model, which includes the stages of planning, action, observation, and reflection. The research subjects consisted of three students, two females and one male. Data were obtained through observation and early reading tests in each cycle. Data analysis was conducted by comparing the average pretest, posttest cycle I, and posttest cycle II scores to see the changes in ability at each stage. The results showed a significant increase from the pretest to the posttest in cycle I and cycle II. These findings confirm that big books are effective in helping children with mild intellectual disabilities recognise letters, read syllables, and understand simple words as the basis for early reading skills.